Host Skin during Tick Infestation: : Unearthing the Local Immunity to Lead an Anti-Tick Vaccine - João, Benvindo; Parizi, Luís Fernando; Zhou, Jinlin; Konnai, Satoru; Termignonni, Carlos; da Silva Vaz Júnior, Itabajara (Acta Scientiae Veterinariae, 2025)
Background: The host skin is the first line of defense against most microorganisms and parasites such as bacteria, fungi and ticks. The immune system present in skin takes part of a sophisticate defense mechanism, firstly as physical, cellular and chemical barriers, followed by a wide range of antimicrobial molecules and specialized immune cells. These cells are responsible for inflammatory processes, antigen uptake and presentation, allergic responses that untimely could control the pathogens. Review: Concerning tick parasitism, skin immunity has a paramount role during tick attachment and blood feeding through both the innate and adaptive responses. In recent years, an increasing number of discoveries in tick physiology revealed a more detailed picture of the role of immune cells and their mediators against tick parasitism. Therefore, a systematic review and summarization of this information can give a more comprehensive understanding of the orchestration of the diverse and complex host immune response mechanisms that reject at least part of infesting ticks and give clues to suggest potential applications to develop better methods for tick control. Conclusion: The local skin immune response to tick and other ectoparasite infestations is intricately influenced by the microenvironment created by parasite attachment components and secreted proteins, attracting and engaging local immune cells. Host immune status further contributes to this dynamic. This review discusses the major cellular responses, functional diversity, and host skin immunity mechanisms stimulated by ticks. However, more research is needed to fill existing gaps and fully understand how the skin responds to ticks and other parasites. For example, studying B-cell responses, their diversity, and exploring the full Th2 immune response could provide valuable insights for improving tick control strategies. Keywords: tick, skin, immunity, parasite, vaccine